Dancing with and for others in the field and postcolonial encounters - Tamisari, Franca (Mimesis Journal, 2024)
Drawing from my research in Northeast Arnhem Land, Northern Territory, Australia, I show how Indigenous dancing embodies statements about being-in-the-world and being-with-others and, from a performance perspective based on participation, I explore the sensuous and affective nature of intercorporeality in relation to the transmission of knowledge and political negotiations both in the community as well as in the diplomatic encounters with non-indigenous visitors and institutions. Beyond the symbolism of gestures, I explore dance as a way of knowing and empathic understanding that reconfigures meaning and directs experience. Dancing with and for others in the context of Indigenous performances and in fieldwork is thus a modality of co-presence and co-presencing, an encounter which opens the way up to an ever-deepening engagement with others. If in the local contexts, dancing can be a way of knowing and relating with people and the environment, it becomes a ‘performative tactic’ deployed to create a space in which non-Indigenous people are challenged to learn and recognise Indigenous ways of being and are required to participate and respond.